Attitudes toward and training in medications for opioid use disorders: a descriptive analysis among employees in the youth legal system and community mental health centers - Lauren M. O'Reilly; Katherine Schwartz; Steven A. Brown; Allyson Dir; Logan Gillenwater; Zachary Adams; Tamika Zapolski; Leslie A. Hulvershorn; Matthew Aalsma (BMC, 2024)
Abstract Background Research demonstrates gaps in medications for opioid use disorder uptake (MOUDs; methadone, buprenorphine, and naltrexone) especially among adolescents. These gaps may be partly attributable to attitudes about and training in MOUDs among youth-serving professionals. We extended prior research by conducting descriptive analyses of attitudes regarding effectiveness and acceptability of MOUDs, as well as training in MOUDs, among youth legal system (YLS) employees and community mental health center (CMHC) personnel who interface professionally with youth. Methods Using survey data from participants (n = 181) recruited from eight Midwest counties, we examined: (1) differences in MOUD attitudes/training by MOUD type and (2) by respondent demographics, and (3) prediction of MOUD attitudes/training by participant-reported initiatives to implement evidence-based practices (EBPs), workplace culture around EBPs, and workplace stress. Attitudes and training were measured in reference to five MOUD types (methadone, oral buprenorphine, injectable buprenorphine, oral naltrexone, injectable naltrexone) on three subscales (effectiveness, acceptability, training). Results Wilcoxon signed-rank tests demonstrated that most outcomes differed significantly by MOUD type (differences observed among 22 of 30 tests). Kruskal-Wallis tests suggested MOUD differences based on demographics. For methadone, CMHC providers endorsed greater perceived effectiveness than YLS providers and age explained significant differences in perceived effectiveness. For buprenorphine, CHMC providers viewed oral or injectable buprenorphine as more effective than YLS employees, respondents from more rural counties viewed oral buprenorphine as more effective than those from less rural counties, and age explained differences in perceived effectiveness. For naltrexone, perceived gender differed by gender. Hierarchical ordinal logistic regression analysis did not find an association between personal initiatives to implement EBPs, workplace culture supporting EBPs, or workplace stress and effectiveness or acceptability of MOUDs. However, personal initiatives to implement EBPs was associated with training in each MOUD. Conclusions These results highlight a few key findings: effectiveness/acceptability of and training in MOUDs largely differ by MOUD type; setting, rurality, age, gender, and education explain group differences in perceived effectiveness of and training in MOUDs; and implementing EBPs is associated with training in MOUDs. Future research would benefit from examining what predicts change in MOUD attitudes longitudinally.